The correlation between serum levels of laminin, type IV collagen, type III procollagen N-terminal peptide and hyaluronic acid with the progression of post-COVID-19 pulmonary fibrosis - Yu, Dapeng; Yin, Guangyue; Lei, Jing; Gong, Yijun; Zheng, Liang; He, Dahui; Lei, Lihua; Sun, Lei (Frontiers in Cell and Developmental Biology, 2024)
COVID-19 patients often suffer from post-COVID-19 acute sequelae (PASC). Pulmonary fibrosis has the most significant long-term impact on the respiratory health of patients, known as post-COVID-19 pulmonary fibrosis (PC19-PF). PC19-PF can be caused by acute respiratory distress syndrome (ARDS) or COVID-19-induced pneumonia. Individuals who experience COVID-19 pneumonia symptoms (including cough, shortness of breath, dyspnea on exertion, and desaturation) for at least 12 weeks after diagnosis, almost all develop PC19-PF. Extracellular matrix molecules: laminin (LN), type IV collagen (IV Col), procollagen III N-terminal peptide (PIIINP), and hyaluronic acid (HA) are involved in the development and progression of PC19-PF. This study aimed to investigate the relationship between the progression of PC19-PF and serum levels of laminin, IV COL, PIIINP, and hyaluronic acid. This retrospective study included 162 PC19-PF patients treated and 160 healthy controls who received treatment at Shenzhen Longgang District Third People’s Hospital, Hebei PetroChina Central Hospital and Changzhi People’s Hospital from January 2021 to December 2023. Serum levels of LN, IV COL, PIIINP, and HA were detected by chemiluminescence immunoassay using commercial kits. Predicted forced vital capacity percentage (FVC% pred), predicted carbon monoxide lung diffusion capacity percentage (DLCO% pred), high-resolution computed tomography (HRCT) scores were assessed, and patient mortality was compared with healthy controls. Serum levels of LN, IV Col, PIIINP, and HA were significantly higher in PC19-PF or CTD-ILD patients than in healthy controls (all p < 0.05), and they were further elevated in acute exacerbation cases (all p < 0.01). In patients, HA was positively associated with HRCT scores and negatively associated with FVC% pred and DLCO% pred (all p < 0.05). Serum levels of LN, IV COL, PIIINP, and HA were significantly lower in surviving patients than in those who deceased (all p > 0.05). Serum levels of LN, IV C, PIIINP, and HA may affect the progression of PC19-PF and may serve as indicators of PC19-PF severity.